HTML
--> --> -->The dependence of the vorticity amplitude on the collision energy and centrality was studied in [16] for the initial state of QGP and further simulated in [17] with a multi-phase transport model (AMPT) for the whole period of QGP evolution. Given that the qualitative predictions are reasonable, it is believed that the traditional understanding of the vorticity may not be completely wrong. Thus, according to concepts from kinetic theory, quantum Wigner functions, and hydrodynamics, various attempts [5, 14, 18-25] have been made to fix the conventional theory, which is based on the straightforward scenario of parton collisions, such as different vorticity definitions by considering the thermal environment [15, 26] and novel vacuum structures by the strongly rotating system [27]. In most of these studies, quarks, which serve as the visible spin-carriers of the final-state hadrons, have attracted notable interest [28, 29]. Gluons, which carry double spins and thus suffer double polarization effects, are neglected because of technical problems in most cases. Given that gluons are closely related with the fundamental problem of quantum chromodynamics (QCD), in this study, we took the first step toward the inclusion of gluons, that is, we studied the vector field in the presence of a background rotation field.
A strong background field changes the vacuum structure of a system drastically in both classical and quantum mechanics [30]. The Landau level is the most famous example in which the system is in a background magnetic field. In such a case, the usual set of plane-wave states would no longer be suitable as a starting point of perturbation. However, the standard quantum field theory on textbooks roots in assuming that the in and out states are plane-wave, which is natural in high energy collisions. Therefore, in a rapidly and globally rotating system, a difficult but straightforward alternative is to reformulate the perturbation computation in principle. In this study, we completed the first step, which includes solving the Proca equation in presence of a background rotation and completing its canonical quantization. We show that because of the symmetry, the eigen states are actually the same as the ones of Maxwell equations in cylindrical coordinates [31-33]. The propagator as well as the near-central approximation were obtained by assuming that the vorticity areas are very small in the relativistic QGP. We will discuss the subtle zero-mass and gauge-symmetry topics in such a curved space-time system in future studies.
In this study, the Latin and Greek indexes represent components of vectors/tensors in the local rest/inertial frame and curved frame respectively, such as
$ X^a = e^a_{\ \mu}X^\mu .$ ![]() | (1) |
$ \begin{array}{l} e_{\ \mu}^{a} = \left( \begin{array}{cccc} 1 & 0 & 0 & 0 \\ v_1 & 1 & 0 & 0 \\ v_2 & 0 & 1 & 0 \\ v_3 & 0 & 0 & 1 \\ \end{array} \right),\;\;\;\; e^{\ \mu}_{a} = \left( \begin{array}{cccc} 1 & -v_1 & -v_2 & -v_3 \\ 0 & 1 & 0 & 0 \\ 0 & 0 & 1 & 0 \\ 0 & 0 & 0 & 1 \\ \end{array} \right). \end{array} $ ![]() | (2) |
$ \begin{array}{l} \eta_{ab} = g_{\mu\nu}e_{a}^{\ \mu}e_{b}^{\ \nu}, \end{array} $ ![]() | (3) |
$ \begin{array}{l} e^a_{\ \mu}e^{\ \mu}_{b} = \delta^a_{b}, \end{array} $ ![]() | (4) |
$ \begin{array}{l} e^{\ \mu}_{a}e^a_{\ \nu} = \delta^\mu_{\nu}, \end{array} $ ![]() | (5) |
$ \begin{array}{l} g_{\mu\nu} = \left( \begin{array}{cccc} 1-v_1^2-v_2^2-v_3^2 & -v_1 & -v_2 & -v_3 \\ -v_1 & -1 & 0 & 0 \\ -v_2 & 0 & -1 & 0 \\ -v_3 & 0 & 0 & -1 \\ \end{array} \right). \end{array} $ ![]() | (6) |
We extracted the rotation effects by constructing the Proca Lagrangian density with respect to the field in the local inertial frame. According to the general relativistic principle, it should be the same as the flat one except for all the quantities that are in the curved space-time. By using relation 3, the vector Lagrangian density could be written as
$ \mathcal{L}_{v} = -\frac{1}{4}F^{\mu\nu}F_{\mu\nu}+\frac{1}{2}m^2 A^2 = -\frac{1}{4}F^{ab}F_{ab}+\frac{1}{2}m^2 A^2, $ ![]() | (7) |
$ \begin{array}{l} D_a A_b = e_a^{\ \mu}D_\mu A_b = e_a^{\ \mu}(\partial_\mu A_b+\Gamma_{\mu b c}A^c), \end{array} $ ![]() | (8) |
$ \begin{aligned}[b] \Gamma_{\mu a b} =& \eta_{ac}[e^c_{\ \nu} e^{\ \lambda}_b G^\nu_{\ \mu\lambda}-e^{\ \lambda}_b\partial_\mu e^c_{\ \lambda}]\\ =& \eta_{ac}(\delta^c_{\ \nu}+\xi^c_{\ \nu})(\delta^{\ \lambda}_b+\xi^{\ \lambda}_b)\frac{1}{2}g^{\nu\alpha}(\partial_\mu h_{\alpha\lambda}+\partial_\lambda h_{\alpha\mu}-\partial_\alpha h_{\mu\lambda})\\&-\eta_{ac}(\delta^{\ \lambda}_b +\xi^{\ \lambda}_b)\partial_\mu(\delta^c_{\ \lambda}+\xi^c_{\ \lambda})\\ =& \eta_{ac}(\delta^c_{\ \nu})(\delta^{\ \lambda}_b)\frac{1}{2}\eta^{\nu\alpha}(\partial_\mu h_{\alpha\lambda}+\partial_\lambda h_{\alpha\mu}-\partial_\alpha h_{\mu\lambda})\\ &-\eta_{ac}(\delta^{\ \lambda}_b)\partial_\mu(\xi^c_{\ \lambda})\\ =& \frac{1}{2}(\partial_\mu h_{a b}+\partial_b h_{a \mu}-\partial_a h_{\mu b})-\partial_\mu \xi_{a b} , \end{aligned} $ ![]() | (9) |
$ \begin{aligned}[b] \Gamma_{0 i j} =& \frac{1}{2}(-\partial_j v_i+\partial_i v_j) = \epsilon_{ijm}\omega_m,\\ \Gamma_{i 0 j} =& -\frac{1}{2}(\partial_j v_i+\partial_i v_j),\\ \Gamma_{i j 0} =& \frac{1}{2}(\partial_j v_i+\partial_i v_j). \end{aligned} $ ![]() | (10) |
Substituting the covariant derivation into the Lagrangian density, a straightforward calculation shows that in the local flat frame the field strength tensor is modified by the rotation as
$ \begin{aligned}[b] F_{0i} =& -F^{0i} = (\partial_0 A_i-\partial_i A_0)-v_j\partial_j A_i-\epsilon_{ijk}\omega_k A_j,\\ F_{ij} =& F^{ij} = \partial_i A_j-\partial_j A_i. \end{aligned} $ ![]() | (11) |
$ \begin{aligned}[b] \mathcal{L}_{v}(\vec\omega) =& \mathcal{L}_{v}(\vec\omega = 0)+\delta\mathcal{L}_{v}(\vec\omega)\\ =& \mathcal{L}_{v}(\vec\omega = 0)-v_j f_{j i}f_{0i}+\frac{1}{2}(v_j\partial_j A_i+\epsilon_{i j m}\omega_m A_j)^2, \end{aligned} $ ![]() | (12) |
The corresponding equations of motion are obtained as
$ \begin{array}{l} \partial_i f_{i 0}-m^2 A_0 = \Delta A_0-m^2 A_0 = 0, \end{array} $ ![]() | (13) |
$ \begin{aligned}[b] \partial^2_0 A_i-&\Delta A_i -2v_j \partial_0\partial_j A_i+(\partial_j v_i-\partial_i v_j)\partial_0 A_j\\+& v_j\partial_j(v_n\partial_n A_i+2\epsilon_{i n m}\omega_m A_n)-(\omega^2 A_i-\omega_n \omega_i A_n)\\+ & m^2 A_i = 0. \end{aligned} $ ![]() | (14) |
$ \begin{aligned}[b]& A_{ TE} = \left( \begin{array}{c} A_0\\ A_{\rho}^{ TE} \\ A_{\phi}^{ TE} \\ A_{z}^{ TE} \end{array} \right) = \left( \begin{array}{c} 0\\ \dfrac{n}{k_t\rho}J_{n}(k_t\rho) \\ \dfrac{\rm i}{k_t}\partial_\rho J_n(k_t\rho) \\ 0 \end{array} \right) {\rm e}^{{\rm i} (n\phi+ k_z z- E_{n k_t k_z} t)}, \\& A_{ TM} = \left( \begin{array}{c} A_0\\ A_{\rho}^{ TM} \\ A_{\phi}^{ TM} \\ A_{z}^{ TM} \end{array} \right) = \left( \begin{array}{c} 0\\ \dfrac{k_z}{E_k k_t}\partial_\rho J_n(k_t\rho) \\ {\rm i}\dfrac{n k_z}{E_k k_t\rho}J_{n}(k_t\rho) \\ -{\rm i}\dfrac{k_t}{E_k}J_n(k_t\rho) \\ \end{array} \right){\rm e}^{{\rm i} (n\phi+ k_z z- E_{n k_t k_z}t)}, \end{aligned} $ ![]() | (15) |
$ \begin{array}{l} A_L = \left( \begin{array}{c} \dfrac{k_z}{E_{kt}}\\ 0 \\ 0 \\ -\dfrac{E_k}{E_{kt}} \\ \end{array} \right)J_n(k_t\rho) {\rm e}^{{\rm i} n\phi}{\rm e}^{{\rm i} k_z z}{\rm e}^{-{\rm i} E_{n k_t k_z} t}, \end{array} $ ![]() | (16) |
As the uniform rotation preserves the cylindrical symmetry, we expect that these solutions are eigen states of the rotation case as well, with a modified energy. By substituting them into Eq. (14) we find that the equations are satisfied if the energy is solved from
$ \begin{array}{l} (-E_{n k_t k_z}^2+E_k^2-2E_{n k_t k_z}\omega n-\omega^2 n^2)\vec{A} = 0. \end{array} $ ![]() | (17) |
The nontrivial difference between these solutions and the usual plane-wave case is that the following properties are satisfied
$ \begin{array}{l} \nabla\times\vec{A}_{ TE} = E_k \vec{A}_{ TM}, \end{array} $ ![]() | (18) |
$ \begin{array}{l} \nabla\times\vec{A}_{ TM} = E_k \vec{A}_{ TE}. \end{array} $ ![]() | (19) |
$ \begin{array}{l} \nabla\times\vec{A}_{1}^{pw} = {\rm i}|\vec k||\vec{A}^{pw}_1|/|\vec{A}^{pw}_2| \vec{A}^{pw}_2, \end{array} $ ![]() | (20) |
$ \begin{array}{l} \nabla\times\vec{A}_{2}^{pw} = -{\rm i}|\vec k||\vec{A}^{pw}_2|/|\vec{A}^{pw}_1| \vec{A}^{pw}_1. \end{array} $ ![]() | (21) |
$ \begin{array}{l} \nabla\times\vec{A}_+ = E_k \vec{A}_+ , \end{array} $ ![]() | (22) |
$ \begin{array}{l} \nabla\times\vec{A}_- = -E_k \vec{A}_-. \end{array} $ ![]() | (23) |
$ \begin{array}{l} \vec{E}_+ = \partial_0 A^+_i = -{\rm i} E_{n k_t k_z}A^+_i, \end{array} $ ![]() | (24) |
$ \begin{array}{l} \vec{B}_+ = -\epsilon_{i j k} \partial_j A^+_k = -E_k A^+_i, \end{array} $ ![]() | (25) |
$ \begin{array}{l} \vec{E}_- = \partial_0 A^-_i = -{\rm i} E_{n k_t k_z}A^-_i, \end{array} $ ![]() | (26) |
$ \begin{array}{l} \vec{B}_- = -\epsilon_{i j k} \partial_j A^-_k = E_k A^-_i. \end{array} $ ![]() | (27) |
$ \begin{array}{l} B_L = A_L-\alpha A_{ TM}, \end{array} $ ![]() | (28) |
$ \begin{array}{l} B_L\cdot A_{ TM} = 0. \end{array} $ ![]() | (29) |
$ \begin{aligned}[b] & \int\rho {\rm d}\rho {\rm d}\phi {\rm d}z A^\mu_{{ TE,TM}, L} A_{\mu, { TE, TM}, L}\\ =& -(2\pi)^2\delta_{mn}\delta(k_z-p_z)\frac{1}{k_t}\delta(k_t-p_t). \end{aligned} $ ![]() | (30) |
$ A_\mu = \sum\limits_{n, \lambda}\int \frac{{\rm d} k_z {\rm d} k_t}{2\pi \sqrt{2E_k}} {\rm e}^{-{\rm i} E_n t}{\rm e}^{{\rm i} k_z z}{\rm e}^{{\rm i} n \phi} a_{n k_t k_z} A_{\mu, \lambda}+{\rm h.c.}, $ ![]() | (31) |
$ \begin{array}{l} [a_{n k_t k_z}, a^\dagger_{m p_t p_z}] = \delta_{m n}\delta(k_z-p_z)k_t\delta(k_t-p_t). \end{array} $ ![]() | (32) |
$ \begin{aligned}[b] D_{\mu\nu}(x, y) =& \langle 0|T A_\mu(x)A_\nu(y)|0\rangle\\ =& \theta(t-s)\langle 0|A_\mu A_\nu|0\rangle+\theta(s-t)\langle 0|A_\nu A_\mu|0\rangle, \end{aligned} $ ![]() | (33) |
$ \begin{aligned}[b] D_{\mu\nu}(x, y) =& \frac{\rm i}{(2\pi)^3}\sum\limits_{n, \lambda}\int {\rm d} k_0 {\rm d} k_z k_t {\rm d} k_t {\rm e}^{{\rm i} k_z (z-\zeta)}{\rm e}^{{\rm i} n (\phi-\theta)}\\ & \times {\rm e}^{-{\rm i}(k_0-n\omega)(t-s)} \frac{ A_{\mu,\lambda}(k_t, n, k_z;\rho)A^*_{\nu,\lambda}(k_t, n, k_z;r)}{k_0^2-E_k^2+i\eta}\\ =& \frac{\rm i}{(2\pi)^3}\sum\limits_{n, \lambda}\int {\rm d} k_0 {\rm d} k_z k_t {\rm d} k_t {\rm e}^{{\rm i} k_z (z-\zeta)}{\rm e}^{{\rm i} n (\phi-\theta)}\\ & \times {\rm e}^{-{\rm i} k_0(t-s)} \frac{ A_{\mu,\lambda}(k_t, n, k_z;\rho)A^*_{\nu,\lambda}(k_t, n, k_z;r)}{(k_0-n\omega)^2-E_k^2+i\eta} \end{aligned} $ ![]() |
$ \begin{aligned}[b] \times {\rm e}^{-{\rm i} k_0(t-s)} \frac{ A_{\mu,\lambda}(k_t, n, k_z;\rho)A^*_{\nu,\lambda}(k_t, n, k_z;r)}{(k_0-n\omega)^2-E_k^2+i\eta}, \end{aligned} $ ![]() | (34) |
![]() | (35) |
In order to make the expression more compact, we use the following symbols
$ \begin{aligned}[b] M_n^{++} =& Z^+_n(\rho,\phi)Z^{+*}_n(r, \theta),\quad M_n^{+-} = Z^+_n(\rho,\phi)Z^{-*}_n(r, \theta),\\ M_n^{-+} =& Z^-_n(\rho,\phi)Z^{+*}_n(r, \theta),\quad M_n^{–} = Z^-_n(\rho,\phi)Z^{-*}_n(r, \theta), \end{aligned} $ ![]() | (36) |
$ \begin{aligned}[b] N_n^{1+} =& Z^+_n(\rho,\phi)J_n(r), \quad N_n^{1-} = Z^-_n(\rho,\phi)J_n(r),\\ N_n^{2+} =& J_n(\rho)Z^{+*}_n(r,\theta),\quad N_n^{2-} = J_n(\rho)Z^{-*}_n(r, \theta), \end{aligned} $ ![]() | (37) |
$ \begin{array}{l} \Pi_n = J_n(\rho)J_n(r), \end{array} $ ![]() | (38) |
$ \begin{array}{l} \sum\limits_n {\rm e}^{{\rm i}n(\phi-\phi')}J_n(k_t\rho)J_n(k_t\rho') = J_0(k_t|\vec{\rho}-\vec{\rho}'|), \end{array} $ ![]() | (39) |
$ \begin{aligned}[b] \int_0^{2\pi}{\rm d}\xi {\rm e}^{{\rm i}kr {\rm cos}\xi}{\rm cos}(\xi+\alpha) =& 2\pi {\rm i cos}\alpha J_1(k r),\\ \int_0^{2\pi}{\rm d}\xi {\rm e}^{{\rm i}kr {\rm cos}\xi}{\rm sin}(\xi+\alpha) =& 2\pi {\rm i sin}\alpha J_1(k r), \end{aligned} $ ![]() | (40) |
$ \begin{aligned}[b] & \int_0^{2\pi}{\rm d}\xi {\rm e}^{{\rm i}kr {\rm cos}\xi}{\rm cos}(\xi+\alpha){\rm cos}(\xi+\alpha) = \pi J_0(k r)-\pi {\rm cos}2\alpha J_2(k r),\\& \int_0^{2\pi}{\rm d}\xi {\rm e}^{{\rm i}kr {\rm cos}\xi}{\rm sin}(\xi+\alpha){\rm sin}(\xi+\alpha) = \pi J_0(k r)+\pi {\rm cos}2\alpha J_2(k r),\\ & \int_0^{2\pi}{\rm d}\xi {\rm e}^{{\rm i}kr {\rm cos}\xi}{\rm cos}(\xi+\alpha){\rm sin}(\xi+\alpha) = -\pi {\rm sin}2\alpha J_2(k r). \end{aligned} $ ![]() | (41) |
![]() | (42) |
Although
![]() |
$ \begin{array}{l} D^{n = 1}_{\mu\nu}(k_t, k_z, \rho) = \dfrac{1}{4}\left( \begin{array}{cccc} 0 & -2{\rm i}\dfrac{k_t E_k}{m^2} J_1 & -2\dfrac{k_t E_k}{m^2} J_1 & 0 \\ 0 & 2J_0 {\rm e}^{-{\rm i}\phi}+\dfrac{k_t^2}{m^2}Z^-_{1}(\rho,\phi) & -2 {\rm i} J_0 {\rm e}^{-{\rm i}\phi}-{\rm i} \dfrac{k_t^2}{m^2}Z^-_{1}(\rho,\phi) & 0 \\ 0 & 2 {\rm i} J_0 {\rm e}^{-{\rm i}\phi}+{\rm i}\dfrac{k_t^2}{m^2}Z^+_{1}(\rho,\phi) & 2J_0 {\rm e}^{-{\rm i}\phi}+\dfrac{k_t^2}{m^2}Z^+_{1}(\rho,\phi) & 0 \\ 0 & 2 {\rm i} \dfrac{k_t k_z}{m^2}J_1 & 2 \dfrac{k_t k_z}{m^2}J_1 & 0 \end{array} \right). \end{array} $ ![]() |
This is a preliminary study on the complete framework of solving the quantum field problems defined in a curved coordinate. In such a case, the translation symmetry will be broken and so will the usual energy-momentum conservation at interaction vertices because the momenta are no longer good quantum numbers when the space is not flat. We also showed that although the computation is much more complicated, the standard process is straightforward for the interaction-free case. However, it could be expected that the interaction terms will induce more fundamental problems, especially for the p-wave cases, e.g.,